Interface structures and electrical properties of W/Si films grown by LPCVD - Atici, Yusuf; Yakinci, M. Eyüphan; Ulu?, Bülent; Aydo?du, Yildirim (TUBITAK, 1996)
Interface structures of W films on Si(100) substrates grown by LPCVD from a mixture of WF6, H2 and SiH4 (silane) gases at 280°C have been studied by transmission electron microscopy. Cross-sectional and plan-view samples were prepared to characterize the films. Consequently, according to the growth conditions, it has been observed that the W-Si interfaces are rough on a fine scale with some more extensive W protrusions in one of the samples which had an extended initial exposure to WF6. The W films have exhibited many randomly oriented grains ranging between 1000 and 4500 Å in size. Sheet resistance measurements have also been evaluated by means of four-point contact method at low temperatures (47-300 K) and it has been detected that the sheet resistance of a film decreases as the temperature decreases. © Tübi?tak.